METHODS KANGAROO AND BABY MASSAGE TO IMPROVE THE BODY WEIGHT ESSPECIALLY TO LOW BIRTH WEIGHT - Siti Maryati; Murti Krismiyati; Dwi Suryanti (Jurnal Kesehatan Karya Husada, 2014)
Background : The results of the Demographic and Health Survey in 2012 showed that the infant mortality rate in the province has a relatively higher rate at 25 per 1,000 live births. In the space of Public General Hospital Wates Kulon Progo in NICU departement on 2012 that 63.16% of infant deaths due to less birth weight . Efforts are already underway to increase in birth weight lessinfants Body Weight in hospitals Wates is the Kangaroo Mother Care ( KMC ). Method of Infant Massage has been done in some hospitals but not yet implemented in this hospital.Objective : The objective of this study was to determine the effectiveness of Infant Massage to Increased Weight especially to Less Birth Weight Infants in NICU departement of public general hospitals Wates Kulon Progo.Methods : This study used a quasi- experimental research design. The experimental group was Newborns with Less Birth Weight Infant Massage given intervention while the control group was Newborns with less birth weight who were given the intervention of Kangaroo Mother Care ( KMC ). After the intervention during the treatment, both groups are seen weight gain, then see the difference. The sample in this study were all newborns with less birth weight were treated in NICU Departement of Public General HospitalWates Kulon Progo. During study met the inclusion criteria and had a total of 18 respondents to the experimental group and 18 respondents for the control group ).Results : The results of measurements preintervensi Body Weight between experimental and control groups were homogeneous with a mean weight ( p value 0.629 ). The mean increase in Body Weight-fed babies Infant Massage intervention of 39.333 grams, while the intervention KMC was given for a mean difference of 33.056 per day increase in Body weight between experimental groups with the control group amounted to 6.277 grams per day. The mean increase in Body Weight-fed babies Infant Massage intervention is greater than the average Body Weight infants given KMC intervention alone.Conclusion : Intervention Infant Massage can effectively improve the less Body weight